Heterologous expression of GH11 xylanase from Myceliophthora heterothallica F.2.1.4 in Pichia pastoris - de Amo, Gabriela Salvador; Bezerra-Bussoli, Carolina [UNESP]; Rodrigues da Silva, Ronivaldo [UNESP]; Kishi, Luciano Takeshi; Ferreira, Henrique [UNESP]; Gomes, Eleni [UNESP]; Bonilla-Rodriguez, Gustavo Orlando [UNESP] (Elsevier, 2024)
This research is centered on improving a xylanase enzyme derived from Myceliophthora heterothallica by expressing it in Pichia pastoris to enhance biomass hydrolysis. Lignocellulosic biomass holds significant potential for renewable applications in biofuels, chemicals, and pharmaceuticals. The study explores the impact of the choice of expression host on enzyme properties, specifically addressing challenges in thermostability by utilizing P. pastoris and leveraging its glycosylation capabilities. Previously expressed in Escherichia coli, the xylanase exhibited in this work cooperative kinetics, pH stability, and resistance to phenolic compounds. Gene integration and expression in P. pastoris were verified through PCR and activity assays. After 120 h of induction, an enzymatic activity of 48.8 U mL−1 was obtained. Subsequent characterization revealed improved specific activity, substrate affinity, and optimal temperature compared to the enzyme expressed in E. coli. The enzyme exhibited excellent pH and temperature stability for industrial applications, maintaining over 90% of its activity within a pH range of 5.0–10.0 and remaining stable even after 90 min of incubation at 55 °C. It also demonstrated resistance to metal ions and responsiveness to phenolic compounds. These findings underscore the versatility of the recombinant xylanase from M. heterothallica expressed in P. pastoris, highlighting its potential as a valuable resource for biomass conversion. The study emphasizes the pivotal role of host choice in optimizing enzyme characteristics for industrial applications, underscoring the importance of employing heterologous expression systems, as demonstrated in this investigation.
Keywords: Heterologous expression; Myceliophthora heterothallica; Recombinant xylanase